Synthesis and Evaluation of Some New Isoquine Analogues for Antimalarial Activity - Chandra Nath Saha; Sanjib Bhattacharya; Dipak Chetia (E-Journal of Chemistry, 2009)
Amodiaquine is a 4-aminoquinoline antimalarial that can cause adverse side effects including hepatic and haematological toxicity. The drug toxicity involves the formation of an electrophilic metabolite, amodiaquine quinoneimine (AQQI), which binds to cellular macromolecules leading to hepatotoxicity and agranulocytosis. Interchange of the 3ʼ hydroxyl and the 4ʼ Mannich side-chain function of amodiaquine provides an amodiaquine regioisomer (isoquine) that cannot form toxic quinoneimine metabolites. By a simple two-step procedure, four isoquine analogues were synthesized and subsequently evaluated against the chloroquine sensitive RKL-2 strain of Plasmodium falciparum in vitro. All synthesized analogues demonstrated differential level of antimalarial activity against the test strain. However, no compound was found to exhibit better antimalarial property as compared to chloroquine.